The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018 SpaceOps Conference 2018
DOI: 10.2514/6.2018-2642
|View full text |Cite
|
Sign up to set email alerts
|

10 Years of RADARSAT-2 Operations - Challenges and Improvements

Abstract: RADARSAT-2 is a radar Earth observation spacecraft that has been operated for over ten years. It continues to perform extremely well and exceeds many of its design requirements. The system availability has been maintained at a high level thanks to careful system monitoring and continuously improving operational processes. This paper will summarize the RADARSAT-2 mission in terms of performance history and operational approach. Attention will be given to the major challenges faced during the mission, and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Overall, the experimental results based on a three-hierarchy framework indicated that polarimetric distortions of most GF-3 PolSAR images were similar to ALOS-2 and RADARSAT-2. ALOS-2 and RADARSAT-2 have been widely applied in Earth observations for many years, and their quality is confirmed to meet the users’ requirements [11,12,15,33,37,43,44,45]. The crosstalk accuracy of RADARSAT-2 of −30 dB, the channel imbalance of 0.5 dB in amplitude, and 5 degrees in phase are reported [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the experimental results based on a three-hierarchy framework indicated that polarimetric distortions of most GF-3 PolSAR images were similar to ALOS-2 and RADARSAT-2. ALOS-2 and RADARSAT-2 have been widely applied in Earth observations for many years, and their quality is confirmed to meet the users’ requirements [11,12,15,33,37,43,44,45]. The crosstalk accuracy of RADARSAT-2 of −30 dB, the channel imbalance of 0.5 dB in amplitude, and 5 degrees in phase are reported [46].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in contrast to the PolSAR system of GF-3, another two space-borne polarimetric SAR (PolSAR) systems, ALOS-2/PALSAR-2 (ALOS-2) and RADARSAT-2, both have the sophisticated images quality subsystem (IQS) [5,6]. In addition, infrastructure and procedures designed to support the image quality and calibration operations, substantial and sustainable updates of calibration files, and annual status of the mission have been reported in both systems [5,6,7,8,9,10,11,12,13,14,15,16,17]. Hence, it is essential to evaluate the quality of GF-3 polarimetric data and to achieve the similar quality compared with ALOS-2 and RADARSAT-2.…”
Section: Introductionmentioning
confidence: 99%